PRA-PERANCANGAN ALAT MATERIAL TRANSPORTER UNTUK PROSES PENGGANTIAN PELAT KAPAL DI AREA DOK - Muhammad Syawal; Bagiyo Suwasono; Ali Munazid (JURNAL JALASENA, 2022)
The equipment used for transporter materials is an important part of a shipyard. This is a necessity of the shipyard, especiallythe medium-sized shipyard, which serves to move materials from the warehouse to the field at the production process stage.This manual ship bottom replating activity requires quite a lot of time and workers in the process, so the results obtained areless efficient and uneconomical. In the process of repairing a ship to replating a plate, an obstacle was found, namely therepair of material in the position of the plate at the bottom was very difficult. Basically, the transfer of a material is carriedout by a crane with a certain capacity and conventional methods of using pipes as a means of moving it. Looking at thedevelopment of technology in modern times, it can all be said that technology is already robot-based. Therefore, the design ofa transporter material tool was carried out that could support the work of replating the plates at the bottom of the ship. Theresults obtained from the evaluation of the suitability of the equipment and the application of an information system in the useof transporter materials are information about the list of lifting equipment needed based on the weight of the construction andthe parts to be replating, especially at the bottom. From this modeling, quite efficient results were obtained with softwaresimulations with standard results of 1: 3 from data in the field. It is hoped that the manufacture of the tool model can facilitatethe work of replating the plates on the bottom of the ship.